Depression of human polymorphonuclear leucocyte function by anti-malarial drugs. - Ferrante, A (1986)
The effect of the anti-malarial drugs quinine, chloroquine, pyrimethamine, mefloquine and quinacrine on human polymorphonuclear leucocyte (PMN) function was examined in vitro. In general, all drugs had their greatest effect on PMN iodination reaction and locomotion, intermediate effects on PMN hexose-monophosphate shunt activity, and least effect on PMN adherence. The most potent of these were pyrimethamine and mefloquine. The PMN iodination reaction and locomotion were inhibited between 0.5-1 microgram/ml (congruent to 2-4 X 10(-6) M) pyrimethamine and 1-4 micrograms/ml (congruent to 0.25-1 X 10(-5) M) mefloquine. The study demonstrates that anti-malarial drugs depress PMN functions associated with antimicrobial activity of the cell.